Dynamic model of a 3-DOF redundantly actuated parallel manipulator. (30th September 2016) - Li, Tiemin; Jia, Shi; Wu, Jun
We investigate the dynamic mode of a 3-degree of freedom (DOF) redundantly actuated parallel manipulator by taking the flexible deformation of the limbs into account. The dynamic model is derived using Newton–Euler formulation. Since the number of equations derived from the force and moment equilibrium of the parallel manipulator components is less than the number of unknown variables, the flexible deformation of the limbs is treated as an inequality constraint to find the solution of the dynamic model. The errors of moving platform caused by the flexible deformation of limbs are discussed, and a control strategy is given. To validate the model, the dynamic model is integrated with the control system and compared with the traditional method to minimize the normal driving forces.